Adam B. Chambers, The Revised Ordinances of the City of Saint Louis 304 (1843) - (:unkn) unknown (My University, 1843)
[Ordinances of Kansas City, Misdemeanors, § 10: Every person who shall discharge any cannon or other ordinance, or fire off any carbine, fusil, rifle, musket, gun, pistol, or other arms, or set off any squib or cracker, or fly any kite in the air, within the city, shall be deemed guilty of a misdemeanor. This section shall not apply to the firing of salutes by any military corps, or to the firing of salutes upon any occasion of general public interest.
Keywords: DISCHARGE